PENGARUH PENGGUNAAN MEDIA POHON LITERASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN 43 AMPENAN - Suryani, Indah; Syaiful Musaddat; Asri Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low literacy in Indonesian among students in learning Indonesian is caused by one factor, namely the lack of use of learning media to support student learning outcomes. This research aims to find out how the use of literacy tree media affects the Indonesian language learning outcomes of class V students at SDN 43 Ampenan. The design of this research is a quasi-experimental research type nonequivalent control group design. Data collection techniques use tests and research instruments using student learning outcomes test sheets whose validity has previously been tested. Data analysis prerequisite testing uses the normality test and homogeneity test. Data analysis used the independent sample t-test with the help of SPSS 24.0 for Windows with a significance value of 5%. The research results obtained a value of tcount = 7,439 > ttable = 1,679. Based on the sig (2-tailed) value, it is found to be 0.00 < 0.05 so it can be concluded that Ha is accepted and H0 is rejected. This shows that there is an influence of the use of literacy tree media on student learning outcomes. To find out how the use of literacy tree media affects students' Indonesian language learning outcomes, an effect size test was carried out with the result d = 3.1, which is in the strong influence criteria. This means that the use of literacy tree media has a strong influence on the Indonesian language learning outcomes of class V students at SDN 43 Ampenan.